Retrospective analysis of clinical characteristics and risk factors of differentiated thyroid cancer in children - Chen, Chun; Hang, Lei; Wu, Yan; Zhang, Qing; Zhang, Yifei; Yang, Jun; Xie, Jin; Lu, Jingrong (Frontiers in Pediatrics, 2022)
Background The incidence rate of children with thyroid cancer has an increasing trend. This study aimed to investigate the clinical characteristics and therapeutic approaches of differentiated thyroid cancer (DTC) in Chinese children. Materials and methods From January 1998 to March 2022, 52 cases undergoing surgical resection in Xinhua Hospital affiliated to Shanghai Jiao Tong University were divided by age (≤ 7 years old: n = 14 and 8–13 years old, n = 38). Treatment methods and clinical features were analyzed to evaluate prognostic factors for oncological outcomes. Results Among the 52 cases, the proportion of local invasion in the pre-school group was found to be higher than that in the school-age group (p = 0.01). T stage was significantly different between the two groups (p ≤ 0.05); the proportion of T1–2 was higher in the school-age group (32 cases, 84.2%), while the proportion of T4 was higher in the pre-school group (6 cases, 42.8%) relatively. The postoperative complication rate was dramatically higher in pre-school children (p ≤ 0.05). Additionally, the total thyroidectomy rate in the non-recurrent group was slightly higher than that in the recurrent group (p ≤ 0.05). Over half of the recurrent cases had low T stage and low ATA (American Thyroid Association) risk levels at initial diagnosis (78.3 and 51.4%). Conclusion The local invasion, tumor stage, and recurrent laryngeal nerve (RLN) injury rates of the pre-school group were higher than that of the school-age group, where young age served as a potential hazard in DTC children. Hence, surgeons should emphasize high-risk features and optimize individualized surgical procedures for DTC children.